Mistakes in orthodontic treatment: Kesalahan-kesalahan dalam perawatan ortodonti - Ardiansyah S. Pawinru; Eddy Heriyanto Habar; Wahyuni (Makassar Dental Journal PDGI Makassar, 2023)
Public awareness of the importance of orthodontic treatment to correct malocclusion is increasing. Orthodontic treatment like any other medical treatment can pose a risk to the patient, due to errors that occur during treatment. This literature review aimed to determine the errors that can occur during orthodontic treatment and the risks they can pose to patients. Scientific information relevant to the study topic was collected and synthesized into an article. In general, errors can originate from orthodontic treat-ment, including the type of appliance used, the direction and amount of force applied, the skill of the clinician and the length of treatment. Errors can also originate from the patient, namely biological and behavioral factors of the patient. It is concluded that orthodontic treatment errors and patient factors can cause risks to patients during orthodontic treatment, namely periodontal da-mage, pain, root resorption, tooth devitalization, temporomandibular joint disorders, caries, and enamel damage. A good under-standing of treatment procedures, diagnosis and patient informed consent is needed in order to minimize the risks of orthodon-tic treatment that can occur in patients.